Patient Safety Culture in Hospital Settings Across Continents: A Systematic Review - Hassan Alabdullah; Waldemar Karwowski (Applied Sciences)
Patient Safety Culture (PSC) is the cornerstone of quality healthcare. Prior research has highlighted the critical role of a safety culture in healthcare. The Institute of Medicine (IOM) has emphasized its effectiveness in reducing errors and improving patient care. This systematic review investigated variations in how staff at international hospitals perceive PSC. In addition to assessing the status of patient safety, this investigation offers a comprehensive synthesis of research from multiple countries to inform future research endeavors. It focused on studies published between 2010 and 2024 that used the standardized Hospital Survey on Patient Safety Culture (HSOPSC) tool, versions 1.0 and 2.0. By following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the review identified vital strengths and weaknesses in PSC globally. Despite these variations, two key strengths emerged consistently across studies, particularly in Asia: teamwork within units and a focus on continuous learning. However, healthcare professionals also raised concerns about a punitive environment that discourages error reporting and inadequate staffing levels. Interestingly, nurses held less positive views on some PSC aspects compared to mixed staff. Several PSC areas of concern raised in previous studies have continued to appear in recent studies. These findings highlight the need for a holistic approach to strengthen PSC globally. This includes fostering a just culture that encourages error reporting, addressing staffing shortages, and promoting open communication among all healthcare professionals. Additionally, tailoring interventions to address regional variations is crucial for creating a safer and more supportive environment for patients worldwide.